普罗布考联合阿托伐他汀治疗多发脑血管狭窄合并主动脉弓溃疡斑块病例报道 A Case Report on the Treatment of Multiple Cerebral Vascular Stenosis with Aortic Arch Ulcer Plaque Using Probucol Combined with Atorvastatin - 王艳玲，王雪梅(WANG Yanling, WANG Xuemei ) (Zhongguo cuzhong zazhi, 2024)
预防卒中的发生和复发是缺血性脑血管病防治的首要任务，多发脑血管狭窄合并主动脉弓溃疡斑块的患者缺血性卒中复发的风险显著升高。本文介绍1例普罗布考联合阿托伐他汀治疗多发脑血管狭窄合并主动脉弓溃疡斑块患者的发病和治疗情况。该例患者表现为轻度神经功能缺损，住院期间发现多发脑血管狭窄合并主动脉弓溃疡斑块，在序贯双联抗血小板治疗3个月后持续阿司匹林单药抗血小板治疗，并全程联合普罗布考和阿托伐他汀强化降脂、抗氧化治疗，随访25个月，无卒中复发，且各项影像学和血液学检查指标保持稳定。 Abstract: Preventing the occurrence and recurrence of stroke is the top priority of the treatment strategy for ischemic cerebrovascular disease. Patients with multiple cerebral vascular stenosis and aortic arch ulcer plaques have a significantly increased risk of recurrent ischemic stroke. This paper introduces a case of probucol combined with atorvastatin in the treatment of multiple cerebral vascular stenosis with aortic arch ulcer plaque. This acute ischemic stroke patient presented with mild neurological impairment. During his hospitalization, multiple cerebral vascular stenosis and aortic arch ulcer plaques were discovered. After 3 months of sequential dual antiplatelet therapy, aspirin therapy was continued and combined with probucol and atorvastatin throughout the course for enhanced lipid-lowering antioxidant therapy. After 25 months of follow-up, there was no recurrence of stroke in this patient, and all imaging and hematological indicators remained stable.